Odpowiedź:
3.
[tex] \frac{ {x}^{2} + x - 6}{x + 5} \div \frac{x - 2}{ {x}^{2} + 2x - 15} [/tex]
x+5 nie= 0
x nie= -5
x²+2x-15 nie= 0
delta = 4 - 4×1×(-15)
delta = 4 + 60
delta = 64
pierwiastek z delty = 8
x1 = (-2 + 8)÷2 = 6÷2 = 3
x2 = (-2 - 8)÷2 = -10÷2 = -5
(x-3)(x+5) nie= 0
x nie= 3
x nie= -5
x - 2 nie= 0
x nie= 2
Założenia:
x nie= -5, 2, 3
x²+x-6
delta = 1 - 4×1×(-6)
delta = 1 + 24
delta = 25
pierwiastek z delty = 5
x1 = (-1 + 5)÷2 = 4÷2 = 2
x2 = (-1 - 5)÷2 = -6÷2 = -3
x²+x-6 = (x-2)(x+3)
[tex] \frac{(x - 2)(x + 3)}{x + 5} \times \frac{(x - 3)(x + 5)}{x - 2} [/tex]
(x+3)(x-3) = x² - 9